Copy number amplification of FLAD1 promotes the progression of triple-negative breast cancer through lipid metabolism - Xiao-Qing Song; Tian-Jian Yu; Yang Ou-Yang; Jia-Han Ding; Yi-Zhou Jiang; Zhi-Ming Shao; Yi Xiao (Nature Communications)
Abstract Triple-negative breast cancer (TNBC) is known for frequent copy number alterations (CNAs) and metabolic reprogramming. However, the mechanism by which CNAs of metabolic genes drive distinct metabolic reprogramming and affect disease progression remains unclear. Through an integrated analysis of our TNBC multiomic dataset (n = 465) and subsequent experimental validation, we identify copy number amplification of the metabolic gene flavin-adenine dinucleotide synthetase 1 (FLAD1) as a crucial genetic event that drives TNBC progression. Mechanistically, FLAD1, but not its enzymatically inactive mutant, upregulates the enzymatic activity of FAD-dependent lysine-specific demethylase 1 (LSD1). LSD1 subsequently promotes the expression of sterol regulatory element-binding protein 1 (SREBP1) by demethylating dimethyl histone H3 lysine 9 (H3K9me2). The upregulation of SREBP1 enhances the expression of lipid biosynthesis genes, ultimately facilitating the progression of TNBC. Clinically, pharmacological inhibition of the FLAD1/LSD1/SREBP1 axis effectively suppresses FLAD1-induced tumor progression. Moreover, LSD1 inhibitor enhances the therapeutic effect of doxorubicin and sacituzumab govitecan (SG). In conclusion, our findings reveal the CNA-derived oncogenic signalling axis of FLAD1/LSD1/SREBP1 and present a promising treatment strategy for TNBC.